THE ANALYSIS OF THE ELECTRONIC SYSTEM IN PAS8E10 ACTIVE SPEAKER AT PT HARTONO ISTANA TEKNOLOGI - Kawidjaja, Chandra Hartono; Ginting, Denis (E-JOINT (Electronica and Electrical Journal Of Innovation Technology), 2024)
This paper contains an analysis and understanding of the operation and performance of the Audio PAS8E10 instrument, an active speaker widely used in various audio applications. The PAS8E10 active speaker is known for its superior sound quality, high durability, and advanced features that support various user needs. This paper will also discuss the technical specifications of the PAS8E10, signal path analysis, and include an analysis of key components such as the power supply and internal amplifier. This active speaker is equipped with modern features like Bluetooth connectivity, multiple input options, all of which play an important role in determining the final performance of this product.